Low-complexity TOA estimation using sawtooth-waveform matching in non-coherent impulse radio systems - ZHENG Lin1; FU Jie-lin1; LIU Zheng-hong1; QIU Hong-bing1; LIN Ji-ming1 (Tongxin xuebao, 2011)
In non-coherent impulse system,an acquisition scheme using negative-slope saw-tooth-waveform matching was proposed.The scheme obtained the sub-optimal estimation performance by utilizing the characteristic of multipath profile.In the proposed scheme,the slope of saw-tooth waveform was analyzed to achieve unbiased estimation in NLOS environment,and the theoretical solution of mean-absolute error（MAE） was derived.Simulations verify the outstanding performance of this scheme in NLOS and low signal-to-noise ratio（SNR） environment.